2016
DOI: 10.1136/heartjnl-2016-309283
|View full text |Cite
|
Sign up to set email alerts
|

Five-year clinical performance of a biodegradable polymer-coated biolimus-eluting stent in unselected patients

Abstract: ISRCTN81649913; Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…The prevention of incomplete endothelialisation and ongoing inflammatory response to permanent polymer might have brought better clinical outcomes 10–12. At present, the efficacy and safety of BP-BES are confirmed only for 5 years after the procedure and those beyond 5 years remain to be investigated 13. Moreover, limited data are available on the incidence and risk of bleeding in patients after BP-BES implantation, which has relatively low risk of ST.…”
Section: Introductionmentioning
confidence: 99%
“…The prevention of incomplete endothelialisation and ongoing inflammatory response to permanent polymer might have brought better clinical outcomes 10–12. At present, the efficacy and safety of BP-BES are confirmed only for 5 years after the procedure and those beyond 5 years remain to be investigated 13. Moreover, limited data are available on the incidence and risk of bleeding in patients after BP-BES implantation, which has relatively low risk of ST.…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, esses resultados favoráveis estão de acordo com vários outros ensaios clínicos com SF revestidos com polímeros biodegradáveis, nos quais as taxas de eventos combinados em cinco anos variaram entre 10,0% a 13,4%. [11][12][13][14] No estudo randomizado LEADERS, o grupo de pacientes tratados com um BES semelhante ao stent do DESTINY, apresentou uma taxa de eventos combinados, morte por todas Tabela 1. Características da população do estudo.…”
Section: Discussionunclassified
“…With long-term data available in 89.3% patients, the recently published 5-year data reported cumulative TLR and definite/probable ST rates of 5.3% and 1.1%, respectively. Between years 1 and 5 the TLR and VLST rates were 3.5% and 0.6%, respectively [41]. More recently, the COMPARE II [42] and NEXT [43] trials also showed non-inferiority of the Nobori stent at 5 years and 3 years in regard to safety and efficacy when compared to the Xience-V (Abbott Vascular, Redwood City, CA, USA) and Xience/Promus (Abbott Vascular) stents, respectively.…”
Section: Noborimentioning
confidence: 99%